The role of hedging in carbon markets - Anne Schopp; Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
In the European Emissions Trading System, power generators hold CO2 allowances to hedge for future power sales. First, we model their aggregate hedging demand in response to changes in expectations of future fuel, carbon and power prices from forward prices. This partial equilibrium analysis is then integrated into a two period model of the supply and demand of CO2 allowances considering also emissions impact and banking of allowances by speculative investors. We find that hedging flexibility can balance a CO2 allowance surplus in the range of 1.1 - 1.6 billion t CO2 at discount rates of future carbon allowances between 0 - 10%. If the surplus exceeds this level, then the rate at which today's carbon prices discount expected future prices increases. This points to the value of reducing the surplus estimated to be 2.6 billion t CO2 allowances in 2015 by about 1.3 billion t CO2, thus ensuring that hedging makes a significant contribution to stabilise carbon prices.
Keywords: D84; G18; Q48; 330; Emissions trading schemes; Banking; Power hedging; Discount rates